Lending to the Unbanked: Relational Contracting with Loan Sharks - Kevin Lang; Kaiwen Leong; Huailu Li; Haibo Xu (Institute of Labor Economics (IZA), 2020)
We study roughly 11,000 loans from unlicensed moneylenders to over 1,000 borrowers in Singapore and provide basic information about this understudied market. Borrowers frequently expect to repay late. While lenders do rely on additional punishments to enforce loans, the primary cost of not repaying on time is compounding of a very high interest rate. We develop a very simple model of the relational contract between loan sharks and borrowers and use it to predict the effect of a crackdown on illegal moneylending. Consistent with our model, the crackdown raised the interest rate and lowered the size of loans.
Keywords: K42; L14; 330; illegal lending; enforcement; relational contract